Adnan Hashim Abdul-Wahid Al-khaf L proper Functions n  - Al-khafaji, Adnan (University of Thi-Qar Journal of Science, 2019)
In this paper, the concepts of L proper Functions are defined depending on the definition of L spaces which was presented by (Kelley, J.C. : 1963 in [3]) and the concept of Proper Functions which was presented by (Bourbaki, N. in [1]). Also we used this concept to study some theorms which are related to the concept of proper Functions.